PENERAPAN MODEL PBL (PROBLEM BASED LEARNING) PADA PEMBELAJARAN IPA SISWA KELAS V SD - WULANDARI, ENI (KALAM CENDEKIA PGSD KEBUMEN, 2013)
Abstract: The Application of PBL ( Problem Based Learning) Model in Science of fifth grade at Elementary School. The aim of this research is increase process and product of Science at fifth grade in Mudal State Elementary School with applying PBL model. This research is classroom action research (CAR). The research is done in three cycles, a cycle contain of planning, action, observation, and reflection. The subject is fifth grade in Mudal State Elementary School which is contain 21 students. The product of the research show that application of PBL model can increase process and product of study in Science of fifth grade in Mudal state elementary school. Key word : PBL, learning, science Abstrak: Penerapan Model PBL ( Problem Based Learning) pada Pelajaran IPA Siswa Kelas V SD. Tujuan penelitian ini adalah untuk meningkatkan proses dan hasil belajar mata pelajaran IPA siswa kelas V SD Negeri Mudal dengan menerapkan model PBL. Penelitian ini merupakan penelitian tindakan kelas ( PTK ). Penelitian dilaksanakan dalam tiga siklus, dengan tiap siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas V SD Negeri Mudal yang berjumlah 21 siswa. Hasil penelitian menunjukkan bahwa penerapan model PBL dapat meningkatkan proses dan hasil belajar IPA siswa kelas V SD Negeri Mudal.   Kata Kunci: PBL, pembelajaran, IPA